A Perspective on the Production of Dye-sensitized Solar Modules - Fakharuddin, Azhar; Rajan, Jose; Brown, Thomas M.; Santiago, Francisco Fabregat (Royal Society of Chemistry, 2014)
Dye-sensitized solar cells (DSCs) are well researched globally due to their potential as low-cost photovoltaic (PV) devices especially suited for building and automobile integrated PV (BIPV, AIPV) and portable or indoor light harvesting applications. Since 1991, large monetary and intellectual investments have been made to develop DSCs into deployable technologies, creating a wealth of knowledge about nano-interfaces and devices through an increasing number of research reports. In response to these investments, the dawn of the new millennium witnessed the emergence of a corporate sector of DSC development. Advances in their design, their incorporation on flexible substrates, the development of solid state modules, their enhanced stability in outdoor environments, and their scalable fabrication tools and techniques have allowed DSCs to move from the laboratory to real-life applications. Although photoconversion efficiencies are not on a par with commercially available CIGS or single crystalline silicon solar cells, they possess many features that compel the further development of DSC modules, including transparency, light weight, flexibility, conformability, workability under low-light conditions, and easy integration in buildings as solar windows. In fact, DSC panels have been shown to deliver even more electricity than their silicon and thin film counterparts of similar power ratings when exposed to low light operating conditions due to their workability in such conditions; thus, they are potential market leaders in BIPV and indoor light harvesting photovoltaic technology. However, large area dye-solar modules lack in performance compared to their laboratory scale devices and also suffer from long term stability issues. Herein, we discuss the main factors behind their inferior photovoltaic performance and identify possible opportunities for the design of more efficient DSC modules.